Implementing mobile geographic information system technology in North Carolina to enhance emergency preparedness: Evaluation of associated trainings and exercises - Horney, MA, MPH, PhD, Jennifer; Ramsey, BS, MPH, Steve; Smith, PhD, Mark; Johnson, MPH, Morgan L.; MacDonald, MPH, PhD, Pia D. M. (Journal of Emergency Management, 2011)
In 2004, the North Carolina Division of Public Health initiated the Rapid Response Project to incorporate geographic information system (GIS) technology into public health preparedness and response. In 2007, 17 local health departments (LHDs) received funding, training, and equipment from federal preparedness grant funds to increase epidemiology capacity through the spatial analysis and centralization of public health data.This article describes training and exercises associated with implementing mobile GIS technology at LHDs and presents evaluation findings from associated trainings and exercises. Participant surveys were used to conduct formative, process, and outcome evaluations to assess the effectiveness of training and exercise activities. Pretraining and post-training and exercise surveys were given to LHD staff who received equipment and attended a training course or participated in the statewide exercise. Differences in means between pretraining and post-training and pre-exercise and postexercise were evaluated using t tests. A total of 96 LHD staff completed the pretraining and posttraining evaluation. Fifty-two participants completed the pre-exercise and postexercise evaluation. After attending the 2-day training, participants reported significant improvements in knowledge and comfort using GIS-enabled computers for field data collection and accessing data and map layers from the state’s database (p < 0.05). Following the exercise, participants reported significant improvements in their ability to use GIS-enabled computers to respond to a natural disaster, bioterrorist attack, chemical spill, or a disease outbreak, as well as to perform a routine community health assessment. Enhancement of mobile GIS/global positioning system capacities of LHDs should improve the readiness of North Carolina in public health emergencies. Handheld computers with GIS were highly acceptable to LHD staff for use during routine assessments and emergency responses. Despite limited experience, LHD staff reported feeling more prepared to use mobile and wireless technology for sample selection, mapping, and data collection.